A=(\(\frac{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}{\sqrt{x}\left(\sqrt{x}-1\right)}\)-\(\frac{\left(\sqrt{x}+1\right)\left(x-\sqrt{x}+1\right)}{\sqrt{x}\left(\sqrt{x}+1\right)}\)):(\(\frac{2\left(\sqrt{x}-1\right)^2}{x-1}\)
=\(\left(\frac{x+\sqrt{x}+1-\left(x-\sqrt{x}+1\right)}{\sqrt{x}}\right).\frac{\sqrt{x}+1}{2\left(\sqrt{x}-1\right)}\)
=\(\frac{2\sqrt{x}}{\sqrt{x}}.\frac{\sqrt{x}+1}{2\left(\sqrt{x}-1\right)}\)=\(\frac{\sqrt{x}+1}{\sqrt{x}-1}\)
4x-x = 2+13
3x+x = 1/4
x-0,5x = 4
x- 0,25x = 1
4x- 3/4x + 5 =
3x - x - 7 = 1+x
8x + 2x + 20 = 25- 2x
3 - 1/2x = x - 1
5x - x + 15 = x + 40
6 + x = 22/3 + 2 - x
\(\frac{x^2+3}{x^2+2}=\left(x+1\right)\left(\sqrt{x+1}-1\right)\)
Tính nhanh B = 1 x 2 + 2 x 3 + 3x 4 + 4x 5 + 5x 6 + .... + 99 x 100
Câu 10:
Cho \(\frac{1}{\sqrt{2}+x}\cdot\frac{1}{\sqrt{2}+y}=a\)
Và \(\frac{1}{\sqrt{2}+x}+\frac{1}{\sqrt{2+y}}=b\)
Tìm x + y ( theo a và b )
\(y=\frac{1}{x^2+\sqrt{x}}\sqrt[]{}\sqrt{\sqrt[]{}\sqrt[]{}\frac{\frac{\frac{\frac{ }{ }}{ }}{ }}{ }}\)
18x(19191919/21212121+88888/99999 va 4 2/5+1/3+5 6/9+1/4+2 3/4+2/5 va (5/111111+5/222222-4/3x7x11x13x37)x10101 va 1/2x 2/3x 3/4x 4/5x 5/6x 6/7x 7/8x 8/9x 9/10 va 7/4x (3333/1212 +3333/2020 +3333/3030 +3333/4242)
x + 2x + 3x + 4x + 5x + 6x + 7x + 8x + 9x = 90
1. 4 + x = 7 - 2x
2. 5 + x = 8,3 + 4,7 - x
3. x + 12 = 35 + ½x
4. 6 + x = 7⅓ + 2 - x
5. 20x + 4 = 19,2 + 15x
6. x + 5 = 8 2/5 - 4x
7. 3 (x +1) = 13,5
8. 32 - (32 - x) = 32
9. 5x - 12 3/5 = 0
10. x - 10/3 = 0
P/s : Please, help me 😋😋